Program Aktualisasi Nilai Pancasila Sila Pertama di Lingkungan Anak-anak - Haifan Kabaih; Hilmia Zahratunnisa; Iif Syarifudin; Ilham Zam Zamy; Indri Handayani; Jasmine Kaylla Gemilang; Dian Herdiana; Bobang Noorisnan Pelita8 (AMMA : Jurnal Pengabdian Masyarakat, 2022)
Pancasila is the basis of the Indonesian state, we as Indonesian citizens must realize the values contained in Pancasila, because this Pancasila is the philosophy of life of the Indonesian nation. So to maintain the integrity of the values contained in this Pancasila, a research study was made. This research is focused on actualizing the first principle, namely the Belief in One Supreme God. This study aims to teach children aged 4-10 material about the mandatory attributes for Allah SWT carried out around their respective home environments. The method used is a qualitative method in which there are several parts including, introductions before the activity begins, delivering material, singing together, distributing prizes, and closing activities. The results of this study indicate that the children in our home environment can memorize the obligatory attributes for Allah SWT and their meanings